Türk Kütüphaneciliğinde Bilimsel İletişimin Kalitesi Üzerine… - Zehra Taşkın (Türk Kütüphaneciliği)
The efforts to enhance quality of scientific communication in Turkish Librarianship Journal have been summarized in this editorial.